THE EFFECT OF SEMEN PARAMETERS ON THE OUTCOME OF INDUCED IN VITRO FERTILIZATION (IVF) IN INFERTILE COUPLES: Life Science-Urology - ALEMI, MOHSEN; OMRANI, RASOOL; TARHANI, JAVAD; KHODADADI, BABAK (International Journal of Life Science and Pharma Research, 2019)
Infertility is one of the most important crises in the lifestyle, leading to many problems, for couples. Infertility may be associated with many factors. The aim of this study is to determine the effect of semen parameters on the outcome of Induced in-Vitro Fertilization in infertile women. This study was performed as a retrospective cohort study using infertile couple’s data that was provided by IVF in Hamadan University of Medical Sciences Endometrial and Endometriosis Research Center in 2016. Couples who had a normal semen parameter were compared with couples who had an abnormal semen parameter in terms of the outcome of the intervention, which included the positive increase of the β-HCG titer in two time measurements.The total number of subjects studied was 289, with mean age 30.49 years. The percentage of positive β-HCG (31.21%), incidence of fertilization (30.54%) and pregnancy (29.86%). The frequency of abnormal semen parameters based on WHO criteria in term of mobility was 53.98%, sperm number 32.22%, volume 4.45% agglutination 4.53% and leukocytospermia 12% respectively. There were a significant relationship between morphology>20% (p=0.022) and normal sperm adhesion (p=0.041) with pregnancy incidence. The viscosity and morphology of sperm, are two semen parameters that effects on the success rate of fertility Induced in-Vitro Fertilization method.